Rheumatoid Meningitis Presenting With Acute Parkinsonism and Protracted Non-convulsive Seizures: An Unusual Case Presentation and Review of Treatment Strategies - Pellerin, David; Wodkowski, Michael; Guiot, Marie-Christine; AlDhukair, Hisham; Blotsky, Andrea; Karamchandani, Jason; Vinet, Evelyne; Lafontaine, Anne-Louise; Lubarsky, Stuart (Frontiers in Neurology, 2019)
Rheumatoid meningitis is a rare complication of rheumatoid arthritis. It is associated with substantial morbidity and mortality. The condition may present in a variety of ways and is therefore diagnostically challenging. Uncertainty still exists regarding the optimal treatment strategy. Herein, we describe the case of a 74-year-old man with a history of well-controlled seropositive rheumatoid arthritis on low-dose prednisone, hydroxychloroquine and methotrexate. The patient presented with a several-month history of multiple prolonged episodes of expressive aphasia, right hemiparesis and encephalopathy. Although no epileptiform activity was recorded on repeated electroencephalography, the symptoms fully resolved following treatment with antiepileptic drugs. He subsequently developed acute asymmetrical parkinsonism of the right hemibody. Magnetic resonance imaging revealed subtle enhancement of the leptomeninges over the left frontoparietal convexity. Cerebrospinal fluid analysis revealed a normal cell count and elevated proteins. Histopathologic analysis of a meningeal biopsy revealed nodular rheumatoid meningitis. The patient was treated with corticosteroids and cyclophosphamide, following which he incompletely recovered. This is the first description of rheumatoid meningitis manifesting with acute parkinsonism and protracted non-convulsive seizures. A summary of cases reported since 2005, including data on pathology, therapy and outcomes, along with a discussion on the efficacy of different treatment strategies are provided.